PENGARUH METODE SENAM IRAMA TERHADAP MOTORIK KASAR ANAK USIA 5-6 TAHUN DI TK ISLAM AL-AZHAR KOTA CIREBON - Sundari, Sri; Yudha, Rivo Panji (STKIP Pasundan, 2017)
The purpose of this study was to determine the effect of rhythmic gymnastics on body balance, limb coordination, limb flexibility and limb strength of children aged 5-6 years using a quantitative approach with Pre Experimental with a pretest-posttest with control group design. The study population was all students in Al-Azhar Islamic Kindergarten in Cirebon. Variable X is the Rhythmic Gymnastics Method, and the Y variable is the Gross Motoric Development of Children Aged 5-6 Years The study sample consisted of 15 students using purposive sampling techniques. Data collection techniques used are observation and documentation. Data analysis uses the Independent Sample T Test. The results showed that the average sample after performing the rhythmic gymnastic method was able to increase the children's gross motor skills by an average of 259.00 in the experimental group and 277.33 in the control group. From these results it can be analyzed that all samples of the experimental group have the same results, namely gross motor children after doing more Rhythmic Gymnastics. The conclusion of the study was that there was an effect of the rhythmic gymnastic method on gross motor skills of children aged 5-6 years in the experimental group of 259.00 and in the control group of 277.33 in Al-Azhar Kindergarten students in Cirebon. Suggestions from this study are Al-Azhar Kindergarten students in Cirebon City to routinely do exercises at least 3 times a week.